Prediction of local sintering in laser beam machining of green Y-TZP ceramic. Issue 1 (2020) - Ducobu, François; Rivière-Lorphèvre, Edouard; Demarbaix, Anthonin; Lauwers, Bert
Abstract: Laser beam machining of Y-TZP engineering ceramic material is carried out in green stage to increase the material removal rate. The generation of hot spots may cause local sintering of the ceramic material leading to a decrease of the mechanical properties of the final sintered component. This paper presents the implementation of alternative laser beam paths to reduce the hot spots occurrence. A thermal finite element model has been developed to support the experimental analysis as well as the prediction of local sintering. The experimental validation of the newly developed toolpath strategies confirmed the reduction of local sintering.